Post-synthesis treatment improves the electrical properties of dry-spun carbon nanotube yarns. (15th November 2021) - Watanabe, Takumi; Itoh, Akira; Watanabe, Tomohisa; Kizaki, Takeshi; Inaguma, Masayasu; Hosoi, Atushi; Kawada, Hiroyuki
Abstract: Researchers expect carbon nanotube (CNT) yarns as an alternative to metallic wiring. However, the electrical properties of CNT yarns remain relatively low, necessitating further improvement. In this study, we fabricated CNT yarns by dry-spinning and performed several post-synthesis treatments to enhance the electrical properties. Polymer solution impregnation increased the electrical conductivity 1.82 × and the current capacity 1.58 × , attributable to densification of the CNT yarn bundles. Graphitization (GT) increased the electrical conductivity 2.58 × and the current capacity 1.83 × , attributable to purification of the crystalline structure. Iodinemonochloride/dichloromethane (ICl/DCM) doping increased the electrical conductivity 1.79 × and the current capacity 1.31 × , attributable to the increased electron carrier density. We achieved further enhancement by a two-step treatment—GT and ICl/DCM doping—resulting in a 4.88 × increase in conductivity and reaches a maximum of 5.12 × 10 5 S/m. We observed greater doping effects after GT, which increased the electrical conductivity 1.89 × , whereas doping for pristine CNT yarn only increased the electrical conductivity 1.79 × . The X-ray photoelectron spectra of CNT yarn in each step indicated a positive relationship between the peak area of the π–π∗ transition component and the electrical conductivity. Therefore, we hypothesize that purification of the crystalline structure increases the electron carrier density by doping. Graphical abstract: Image 1 Highlights: Electrical properties of CNT yarns are affected by the post-synthesis treatment. Single treatment is the mostly performed in enhancing the electrical properties. Combination of treatments exhibit even more remarkable enhancement effect. New density states may be produced by the combination of treatments.